Life-Threatening Retroperitoneal Hematoma in a Patient with COVID-19 - Shah, Monarch; Colombo, John Paul; Chandna, Sanya; Rana, Haris (Case Reports in Hematology, 2021)
COVID-19 is a respiratory illness that affects the human body in many different ways. The disease carries both thrombotic and hemorrhagic complications, especially in those patients who are anticoagulated to prevent the thromboembolic manifestations. In this report, we discuss a case of retroperitoneal hemorrhage in a patient treated with therapeutic anticoagulation which ultimately led to the patient’s death. The literature highlights the importance of anticoagulation because it reduces mortality in patients hospitalized with COVID-19. Although, more recent studies suggest that patients treated with therapeutic anticoagulation are at a higher risk of hemorrhage and increased mortality. Therefore, our case stresses the importance of active monitoring of these patients to detect any suspected case of hemorrhage early to reduce mortality. Overall, more research should be conducted to determine the optimal dosing of anticoagulation that balances safety and efficacy.